Etude de l’activité antimicrobienne des fruits de courge et de l’écorce d’orange Thomson - DJABALI Kaouther Nour El-Houda; KIASSA Aya (My University, 2023)
Our study consists in evaluating in vitro the antimicrobial power of the essential oil of the peel of Thomson oranges (Citrus sinensis) and the vegetable oils of the seeds of the two species of squash: Provence musk squash (Cucrbita moschata) and pumpkin squash (Cucurbita pepo). The extraction of the essential oils of C.sinensis was carried out by Hydrodistillation and the extraction of the vegetable oils of the two species of squash was carried out by cold pressure method. Antimicrobial activity was assessed by aromatogram method on eight bacterial species: Escherichia coli (5 strains), Staphylococcus aureus (5 strains), Pseudomonas aeruginosa (3 strains), Klebsiella pneumoniae (5 strains), Proteus mirabilis (2 strains), Salmonella (1 strain), Enterococcus faecalis (1 strain), and one fungal species: Candida albicans (3 strains). The determination of MIC and MBC was performed for the strains that showed the greatest sensitivity to the oils tested. The study of the antibacterial activity of the vegetable oils of the two species of Cucurbita revealed a positive effect on Gram-negative bacteria, with a percentage of 69% for the species C. moschata, and a percentage of 92% for the species C. pepo. The antibacterial activity was also detected against Gram-positive bacteria with a percentage of 100% and 67% for the species C. moschata and C. pepo, respectively. On the other hand, the essential oil of Thomson orange peel was active against 31% and 17% of Gram-negative and Gram-positive bacteria, respectively. Regarding the antifungal activity, we found that 67% of the yeasts tested were sensitive to the action of vegetable oil of the species C. moschata, and only 33% of these yeasts were sensitive to the action of the species C. pepo. Moreover, the essential oil of orange peel was active against 67% of the yeasts tested. P. mirabilis (strain 2) was the most susceptible strain to C. pepo vegetable oil with an MIC of (0. 512 mg/ml) and a CMB of 1,024 mg/ml. On the other hand, S. aureus (strain 2M) was most sensitive to the action of vegetable oil of C. moschata (MIC = 1. 024 mg/ml, CMB = 0. 4096 mg/ml). For the essential oil of C. sinensis was more effective on the E. coli strain (strain 2) (MIC = 1,024 mg/ml, CMB = 0. 4096 mg/ml). The results show the potential effect of the oils studied on the different bacterial and fungal strains tested --------------------------------------------------------------------------------------------------------------------------------------------- : تتكون دراستنا من تقييم الطاقة المضادة للميكروبات للزيت األساسي لقشر البرتقال طومسون والزيوت النباتية لبذور نوعي القرع: القرع المسكي في بروفانس والقرع اليقطين تم استخراج الزيوت عن طريق التقطير المائي وتم استخراج الزيوت النباتية من نوعي القرع بطريقة الضغط البارد. تم تقييم النشاط المضاد للميكروبات بطريقة الروائح على سبعة أنواع بكتيرية : اإلشريكية األساسية من الحمضيات القولونية )5 سالالت( ، المكورات العنقودية الذهبية )5 سالالت( ، الزائفة الزنجارية )3 سالالت( ، الكليبسيال )5 سالالت( ، المتقلبة رائعة )2 سالالت( ، السالمونيال ) ساللة واحدة(، المكورات المعوية ) ساللة واحدة( ، ونوع فطري: المبيضات البيض )3 سالالت(. تم تحديد الحد األدنى من التركيز المثبط والحد األدنى من تركيز البكتريتيد للسالالت التي أظهرت أكبر حساسية تجاه الزيوت المختبرة. كشفت دراسة النشاط المضاد للبكتيريا للزيوت النباتية من نوعي كورج عن تأثير إيجابي على البكتيريا سالبة الجرام، بنسبة 69 ٪ ألنواع القرع المسكي ; ونسبة ٪92 ألنواع القرع. تم الكشف عن قوة مضادة للبكتيريا ضد البكتيريا كان الزيت العطري لقشر البرتقال طومسون نش ًط 31 ٪ و17 ٪ من البكتيريا سالبة الجرام وإيجابية إيجابية الجرام بنسبة 100 ٪ و67 ٪ ألنواع القرع المسكي وقرع اليقطين، على التوالي. من ناحية أخرى، ا ضد الجرام، على التوالي. فيما يتعلق بالنشاط المضاد للفطريات، وجدنا أن ٪67 من الخمائر التي تم اختبارها كانت حساسة لعمل الزيت النباتي ألنواع القرع المسكي؛ و٪33 فقط كانت هذه الخمائر حساسة لعمل أنواع يت العطري لقشر البرتقال نش ًط ٪67 من الخميرة التي تم اختبارها. كانت ساللة المبيضات البيض )2( أكثر السالالت حساسية تحت تأثير زيت اليقطين النباتي قرع اليقطين باإلضافة إلى ذلك، كان الز ا مقابل مع الحد األدنى من التركيز المثبط )0.512 مجم/ مل( و األدنى من تركيز البكترسيد )1.024 مجم / مل( بينما كانت في حين أن المكورات العنقودية كانت األكثر حساسية تحت تأثير زيت النباتي للقرع المسكي ) الحد األدنى من التركيز المثبط = 1.024 مجم / مل ، الحد األدنى لتركيز البكترسيد = 4.096 مجم / مل .مجم / مل 4.096 = الحد األدنى من التركيز المثبط = 1.024 مجم / مل ، الحد األدنى من تركيز البكترسيد. ) (. بالنسبة لزيت البرتقال األساسي كان أكثر فعالية في ساللة اإلشريكية القولونية ) تظهر النتائج التي تم الحصول عليها التأثير المحتمل للزيوت المدروسة على السالالت البكتيرية والفطرية المختلفة التي تم اختباره --------------------------------------------------------------------------------------------------------------------------------------------- Notre étude consiste à évaluer in vitro le pouvoir antimicrobien de l’huile essentielle des écorces d’oranges Thomson (Citrus sinensis) et les huiles végétales des graines des deux espèces de courge : la courge musquéede Provence (Cucrbita moschata) et la courge citrouille (Cucurbita pepo). L’extraction des huiles essentielles de C. sinensis a été réalisée par Hydrodistillation et l’extraction des huiles végétales des deux espèces de courge a été réalisée par la méthode de la pression à froid. L’activité antimicrobienne a été évaluée par la méthode d’aromatogramme sur huit espèces bactériennes : Escherichia coli (5 souches), Staphylococcus aureus (5 souches), Pseudomonas aeruginosa (3 souches), Klebsiella pneumoniae (5 souches), Proteus mirabilis (2 souches), Salmonella (1 souches), Enterococcus faecalis (1 souches), et une espèce fongique : Candida albicans (3 souches). La détermination de la CMI et la CMB a été réalisée pour les souches qui ont démontré la plus grande sensibilité vis-à-vis les huiles testées. L’étude de l'activité antibactérienne des huiles végétales des deux espèces de Cucurbita a révélé un effet positif sur les bactéries à Gram négatif, avec un pourcentage de 69% pour l’espèce C. moschata ; et un pourcentage de 92% pour l’espèce C. pepo. Le pouvoir antibactérien a été également détecté contre les bactéries à Gram positif avec un pourcentage de 100% et 67% pour l’espèce C. moschata et C. pepo, respectivement. D’autre part, l’huile essentielle des écorces d’oranges Thomson était active vis-à-vis 31% et 17% des bactéries à Gram négatif et à Gram positif, respectivement. À propos de l'activité antifongique, nous avons trouvé que 67% des levures testées étaient sensibles à l’action de l’huile végétale de l’espèce C. moschata ; et seulement 33% de ces levures étaient sensibles à l’action de l’espèce C. pepo. Par ailleurs, l’huile essentielle des écorces d’oranges était active contre 67% des levures testées. P. mirabilis (la souche 2) était la souche la plus sensible sous l’action de l’huile végétale de C. pepo avec une CMI de (0.512 mg/ml) et une CMB de 1.024 mg/ml. Tandis que, S. aureus (la souche 2M) était la plus sensible sous l’action de l’huile végétale de C. moschata (CMI = 1.024 mg/ml, CMB = 4.096 mg/ml). Pour l'huile essentielle de C. sinensis était plus efficace sur la souche d’E. coli (la souche 2) (CMI = 1.024 mg/ml, CMB = 4.096 mg/ml). Les résultats obtenus montrent l’effet potentiel des huiles étudiées sur les différentes souches bactériennes et fongiques testées